2012
DOI: 10.1175/mwr-d-11-00045.1
|View full text |Cite
|
Sign up to set email alerts
|

Advection-Based Adjustment of Radar Measurements

Abstract: When making radar-based precipitation products, a radar measurement is commonly taken to represent the geographical location vertically below the contributing volume of the measurement sample. However, when wind is present during the fall of the hydrometeors, precipitation will be displaced horizontally from the geographical location of the radar measurement. Horizontal advection will introduce discrepancies between the radar-measured and ground level precipitation fields. The significance of the adjustment de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…The data are adjusted in situ and output in the same polar format. This is in contrast to the work of Mittermaier et al (2004) and of Lauri et al (2012), who apply corrections to radar CAPPIs (constant-altitude PPIs) and Cartesian composites respectively.…”
Section: Context and Overviewmentioning
confidence: 79%
See 2 more Smart Citations
“…The data are adjusted in situ and output in the same polar format. This is in contrast to the work of Mittermaier et al (2004) and of Lauri et al (2012), who apply corrections to radar CAPPIs (constant-altitude PPIs) and Cartesian composites respectively.…”
Section: Context and Overviewmentioning
confidence: 79%
“…The fall time for this path is calculated and the reflectivity measurement from the appropriate time placed at the surface. A prognostic approach is described in detail by Lauri et al (2012) and illustrated in their Fig. 4.…”
Section: Fall Streak Profile Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hogan and Kew (2005) and Kalesse et al (2016) showed how in situations when vertical wind shear is observed, the evolution of snow particles should be tracked along slanted fall streaks instead of considering vertical profiles. Other studies used the principle to observe hydrometeors with high spatial resolution (Collier 1999) or to improve radar-derived rainfall estimations (Mittermaier et al 2004;Lack and Fox 2007;Lauri et al 2012). Kalesse et al (2016) assumed that the ice-formation process is stationary during cloud observation, and only additional information about the horizontal wind field is needed in order to follow particles through a cloud.…”
Section: Ansmann 2015)mentioning
confidence: 99%
“…to the runway half an hour later. Lauri et al (2012) have discussed the effect of advection in snowfall measurement.…”
Section: Nowcasting Snowmentioning
confidence: 99%